THE RELATIONSHIP OF QUALITY OF SERVICE WITH INTEREST IN REVISIT IN OUTPUT PATIENTS OF INTERNAL DISEASE POLY AT LUBUK PAKAM GRANDMED HOSPITAL - Ardianto Syahputra; Liharnita Saragih; Desika Wali Pardede (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Good service quality will give satisfaction to the patient, which in the end the patient will reuse and recommend the health service to the people around him. So that good and quality service will increase the number of visits which in turn will increase the amount of hospital income. This type of research is a quantitative research that is an analytic survey with a cross sectional design which aims to determine the relationship between service quality and interest in repeat visits of outpatients in the Internal Medicine Polyclinic at Grandmed Lubuk Pakam Hospital which was observed at the same time. The population in this study were all outpatients of the Internal Medicine Polyclinic at Grandmed Lubuk Pakam, totaling 80 people based on an initial survey in 2022 at Grandmed Lubuk Pakam Hospital. The sample in this study were 44 outpatients at Grandmed Lubuk Pakam who were taken using purposive sampling technique. The results of this study indicate that there is no relationship between the quality of health services in the tangible dimensions of rehabilitation (0.386 > 0.05), responsiveness (0.59 > 0.05), assurance (0.68 > 0.05), empathy (0.058 > 0.05), and tangibles (0.023 < 0.05). With interest in repeat patient visits. The conclusion of this study is that there is no relationship with the quality of health services with the interest of repeat visits to outpatients in the Internal Medicine Polyclinic at Grandmed Lubuk Pakam.